2017
DOI: 10.1186/s12974-017-0969-4
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the acute phase response to the pathogenesis of relapse in chronic-relapsing experimental autoimmune encephalitis models of multiple sclerosis

Abstract: BackgroundIncreased relapse rates in multiple sclerosis (MS) as a consequence of peripheral immune system activation, owing to infection for example, have been widely reported, but the mechanism remains unclear. Acute brain injury models can be exacerbated by augmenting the hepatic acute phase response (APR). Here, we explored the contribution of the hepatic APR to relapse in two rodent models of MS.MethodsMice with MOG-CFA-induced chronic relapsing experimental autoimmune encephalitis (CR-EAE) were killed bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…SAA protein was found to be elevated in peripheral blood of patients with relapsing–remitting MS over a 3-month period [23]. In chronic-relapsing (CR) EAE models of MS, the contribution of the response in the acute phase was recently reported [33]. In CR-EAE, SAA1 mRNA was found to be significantly elevated in the liver in mice before the onset of clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…SAA protein was found to be elevated in peripheral blood of patients with relapsing–remitting MS over a 3-month period [23]. In chronic-relapsing (CR) EAE models of MS, the contribution of the response in the acute phase was recently reported [33]. In CR-EAE, SAA1 mRNA was found to be significantly elevated in the liver in mice before the onset of clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to corroborate this notion are data indicating aging-related decrease of Thy-1 expression on the surface of rat DP TCRαβ lo thymocytes followed by a decline in the frequency of post-selected DP TCRαβ hi thymocytes [ 38 ]. Given that catecholamines were shown to downregulate Thy-1 mRNA expression [ 79 ], the decreased surface density of Thy-1 in immunized rats could be also related to data indicating an increase in the circulating levels of catecholamines during active EAE and MS [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal barrier function in ocular BD patients has not yet been investigated and is indeed an interesting area for further research. LPS is one of the most potent gram-negative derived factors that can stimulate Th1 and Th17 cell differentiation and is able to exacerbate experimental autoimmune disease models such as EAU and EAE ( Fang et al, 2010 ; Klaska et al, 2017 ; Mardiguian et al, 2017 ). These findings are also consistent with previous studies in which LPS/TLR4 pathways are involved in the aberrant immune response observed in BD and our result showing a higher abundance of SRB (such as Bilophila species) in the BD-recipient mice ( Liang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%